1997
DOI: 10.1139/m97-026
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of methylotrophic bacteria by electroporation

Abstract: An efficient system for electroporation of the methylotrophic bacteria Hyphomicrobium facilis, Hyphomicrobium denitrificans, Methylobacillus glycogenes, Methylobacterium extorquens, and Methylophilus methylotrophus is described. It could be demonstrated that vectors based on the broad-host-range plasmid pBBR1 could be transferred into these strains. Plasmid pBBR1KAN (3.9 kb), a kanamycin-resistant derivative of pBBR1, was suitable for transformation experiments in these methylotrophic bacteria. Transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…1). The parent plasmid, pBBR122, has been shown to be capable of replicating at medium copy number in at least 26 Gram-negative species and was stably maintained by selective pressure in all Gramnegative organisms tested so far (Antoine & Locht, 1992 ;Elzer et al, 1995 ;Gliesche, 1997 ;Su et al, 2001). Incompatibility tests have shown that pBBR122 does not belong to the IncP, IncQ or IncW groups of broad-hostrange plasmids (Antoine & Locht, 1992).…”
Section: Construction Of the P1 Phagemidmentioning
confidence: 99%
“…1). The parent plasmid, pBBR122, has been shown to be capable of replicating at medium copy number in at least 26 Gram-negative species and was stably maintained by selective pressure in all Gramnegative organisms tested so far (Antoine & Locht, 1992 ;Elzer et al, 1995 ;Gliesche, 1997 ;Su et al, 2001). Incompatibility tests have shown that pBBR122 does not belong to the IncP, IncQ or IncW groups of broad-hostrange plasmids (Antoine & Locht, 1992).…”
Section: Construction Of the P1 Phagemidmentioning
confidence: 99%
“…(13,53) and has been successfully applied in this study. Optimal electrical settings for the electrotransformation of H. chloromethanicum were previously determined to be 2.4 kV and 200 ⍀ at a capacitance of 25 F (53).…”
Section: Resultsmentioning
confidence: 99%
“…Transformation was done by electroporation using a Gene Pulser II electroporation system (Bio-Rad, California, USA). 16) DNA was sequenced with a BigDyeTM Terminator Cycle Sequencing Kit with an ABI model 310A sequencer. DNA sequence analysis was carried out with GENETYX software (Software Development, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%